Rodent abundance dynamics and leptospirosis carriage in an area of hyper-endemicity in New Caledonia. - Julie Perez; Fabrice Brescia; Jérôme Becam; Carine Mauron; Cyrille Goarant (Public Library of Science (PLoS), 2011)
BACKGROUND: Widespread but particularly incident in the tropics, leptospirosis is transmitted to humans directly or indirectly by virtually any Mammal species. However, rodents are recognized as the most important reservoir. In endemic regions, seasonal outbreaks are observed during hot rainy periods. In such regions, hot spots can be evidenced, where leptospirosis is "hyper-endemic", its incidence reaching 500 annual cases per 100,000. A better knowledge of how rodent populations and their Leptospira prevalence respond to seasonal and meteorological fluctuations might help implement relevant control measures. METHODOLOGY/PRINCIPAL FINDINGS: In two tribes in New Caledonia with hyper-endemic leptospirosis, rodent abundance and Leptospira prevalence was studied twice a year, in hot and cool seasons for two consecutive years. Highly contrasted meteorological situations, particularly rainfall intensities, were noted between the two hot seasons studied. Our results show that during a hot and rainy period, both the rodent populations and their Leptospira carriage were higher. This pattern was more salient in commensal rodents than in the sylvatic rats. CONCLUSIONS/SIGNIFICANCE: The dynamics of rodents and their Leptospira carriage changed during the survey, probably under the influence of meteorology. Rodents were both more numerous and more frequently carrying (therefore disseminating) leptospires during a hot rainy period, also corresponding to a flooding period with higher risks of human exposure to waters and watered soils. The outbreaks of leptospirosis in hyper-endemic areas could arise from meteorological conditions leading to both an increased risk of exposure of humans and an increased volume of the rodent reservoir. Rodent control measures would therefore be most effective during cool and dry seasons, when rodent populations and leptospirosis incidence are low.